Volume 2: Dynamics, Vibration and Control; Energy; Fluids Engineering; Micro and Nano Manufacturing 2014
DOI: 10.1115/esda2014-20514
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Turbocharger Cut Out on Two-Stroke Marine Diesel Engine Performance and NOx Emissions at Part Load Operation

Abstract: The diesel engine is widely used for marine vessel propulsion due to its relatively high efficiency compared to existing alternative propulsion systems. The majority of these engines are slow speed two stroke ones. Despite the improvement of their efficiency there now exists a demand for drastic reduction of daily fuel oil consumption as a result of the global financial situation and continuously increasing fuel prices. Towards this effort, slow steaming is a promising solution for the drastic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Although slow steaming is commonly used in the last years, only limited published works have investigated this specific engine operating phases [41][42][43]. Kyrtatos et al [43] proposed a novel way of evaluating engine performance by comparing service monitored data and thermodynamic model predictions, and they carried out a study for predicting a VLCC main engine performance at slow steaming conditions concluding that a sufficient extrapolation of the compressor map is required in order to avoid errors in simulation results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although slow steaming is commonly used in the last years, only limited published works have investigated this specific engine operating phases [41][42][43]. Kyrtatos et al [43] proposed a novel way of evaluating engine performance by comparing service monitored data and thermodynamic model predictions, and they carried out a study for predicting a VLCC main engine performance at slow steaming conditions concluding that a sufficient extrapolation of the compressor map is required in order to avoid errors in simulation results.…”
Section: Introductionmentioning
confidence: 99%
“…Kyrtatos et al [43] proposed a novel way of evaluating engine performance by comparing service monitored data and thermodynamic model predictions, and they carried out a study for predicting a VLCC main engine performance at slow steaming conditions concluding that a sufficient extrapolation of the compressor map is required in order to avoid errors in simulation results. Hountalas et al [42] studied the effect of one turbocharger unit cut-out (out of two) on the engine performance and it is concluded that retard of fuel injection could be the solution for reducing the cylinder maximum pressure and the associated NOx emissions. In [41], a MVEM was used to investigate the engine performance at low load operation considering the influence of blower activation/deactivation phases and turbocharger cut-out.…”
Section: Introductionmentioning
confidence: 99%
“…Ship energy efficiency objective. When the matching procedure objective is to minimise the annual fuel consumption (FC) (calculated by equation (13) for the engine operating profiles shown in Figure 10), the turbocharger with compressor map ID125 was selected for the single turbocharger system. This turbocharger provided the lowest FC, which was found to be 5% lower than the highest calculated FC.…”
Section: Turbocharging System Selectionmentioning
confidence: 99%
“…The engine−turbocharger matching can be a lengthy process for a new marine engine, due to the large number of the involved parameters, 8 which affects the engine transient response, especially at low loads operation, due to the turbocharging system lag. Alternative configurations were proposed for improving the engine performance and transient response including the sequential turbocharging, 9 the two-stage 10,11 turbocharging, the variable geometry turbine turbocharger, 12 the turbocharger cut-out (in cases with multiple turbochargers connected in parallel), 13,14 and the hybrid turbocharger. 15,16 Nonetheless, the single and parallel turbocharging systems are preferred for most of the marine engines, as they constitute solutions of lower complexity, thus imposing less challenges for their installation, control and maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…As a solution, cutting out of a turbocharger supplies a relatively high amount of exhaust gas flow that increases the operating efficiency of the turbine at the engines with more than one turbocharger. 24 The turbocharger cut-out method had been studied for performance analysis 25 and calculation of the energy efficiency design index. 26 To satisfy smooth operation for turbochargers variable turbine area turbochargers, are another solution to increase the turbocharging efficiency.…”
Section: Introductionmentioning
confidence: 99%